Recovery of high-value functional compounds as a strategy for the valorization of fruit residues - Alayla Guadalupe Ibarra-Manzanares; Zaira Guadalupe Ibarra-Manzanares; Lluvia de Abril Alexandra Soriano-Melgar; Mariela Ramona Michel-Michel; Martha Monzerrath Orozco-Sifuentes; José Fernando Solanilla-Duque; Raul Rodriguez-Herrera (Food and Humanity, 2026)

Agricultural sprinkler irrigation systems as environmental reservoirs and airborne dissemination sources of Legionella pneumophila - Fernando González-Camacho; Paula Ruiz-Rodriguez; Irene González; María Guerrero-Vadillo; Mireia Coscollá; Juana María González-Rubio (Journal of Environmental Management, 2026)

Efficiency of emulsion flooding for the removal of organic pollutants from soils: A pore-scale study on the effects of oil volume fraction, injection flow rate, and wettability - Shuxin Wang; Antonio Rodriguez de Castro; Fernando Leal-Calderon; Azita Ahmadi-Senichault; Abdelaziz Omari (Journal of Hydrology, 2026)

Precision Agriculture Approach for Potato Purple Top Disease Detection: Utilizing UAV - Derived Multispectral Imagery and Machine Learning for Symptom Characterization - Diego Fernando Sánchez-Vivas; David Rodriguez Puertas; Pedro Pablo Bacca Acosta; Donald Heberth Riascos-Ortiz (American Journal of Potato Research, 2026)

Trade-off between chemical safety and bioactivity during cocoa roasting revealed by multivariate modeling - Yeison-Fernando Barrios-Rodriguez; María Medina-Orjuela; Danilo Gómez; Jessica P. Jiménez-Ochoa; Claudia Amorocho-Cruz; Carlos Carranza; Joel Girón-Hernández (Food Chemistry, 2026)

Deacetylation and Mechanical Refining Pathway for the Bioconversion of Sugarcane Bagasse - Fernando Roberto Paz Cedeno; Gustavo R. Gomes; Jessica J. Silva; Fabricia F. Menezes; Viviane M. Nascimento; George J. M. Rocha; Renata P. Rodriguez; Xiaowen Chen; Antonio Bonomi; Carlos Driemeier (BioEnergy Research, 2026)
Advancing lignocellulose biorefining is imperative for the deployment of cellulosic (2G) biofuels. This work investigates the tailoring of the alkaline deacetylation and mechanical refining (DMR) pathway for the bioconversion of sugarcane bagasse. Experiments are conducted at laboratory and pilot scales, varying the pretreatment conditions (70–92 °C; 48–100 g NaOH /kg) and the mechanical refining technologies (PFI and disk refining). The pretreatments selectively solubilize acetyl groups (> 86%) and lignin (10–63%) while mostly preserving structural carbohydrates in the solid phase. Enzymatic hydrolysis generates hydrolysates of clean sugars (glucose and xylose), with sugar yields increasing up to 81% for glucose and 89% for xylose in response to delignification and mechanical refining. Biochemical methane potential assays reveal specific methane productions of up to 568 NmL CH₄ gVS⁻¹ for alkaline liquor monodigestion and 344 NmL CH₄ gVS⁻¹ for co-digestion with sugarcane vinasse from the conventional (1G) sugarcane ethanol, indicating a strong potential for bioenergy recovery from this process stream. Synergies are identified in integrating 1G ethanol, 2G DMR processing of bagasse, and anaerobic co-digestion of 1G vinasse and 2G DMR alkaline liquor. This technology enables sugarcane biorefineries to enhance the co-production of ethanol, methane, and concentrated streams of CO 2 .

Fish welfare in a changing world: New developments and current challenges - Sonia Rey Planellas; João L. Saraiva; Eliane Gonçalves‐de‐Freitas; Pablo Arechavala‐Lopez; Bernice Bovenkerk; Michael Breen; Steven J. Cooke; Martin Føre; Lene Northwood; Lars Helge Stien; Sunil Kadri; Chris Noble; et al. (Journal of Fish Biology, 2026)
The welfare of non‐human animals is central to ethical discussions on animal use, with increasing attention to fish welfare across research, aquaria, aquaculture, and fisheries. This paper reviews current theoretical approaches to animal welfare and recent advances in defining and assessing fish welfare since the seminal paper by Huntingford et al. (2006; J Fish Biol 68 : 332–372), highlighting the growing role of cognitive and affective processes. It also includes the concept of positive welfare and some of the current research advances in this field. Methods for measuring, monitoring and assessing welfare via the utilisation of outcome‐ and input‐based indicators are outlined, ranging from practical operational tools to laboratory‐based measures. Welfare concerns in wild‐capture fisheries are examined in relation to stress, flesh quality and sustainability, including the welfare of released fish. Recent advances in fish neurobiology, cognition and pain perception are summarised, together with technological innovations that enhance welfare monitoring and management. The paper also explores the relationship between fish welfare, sustainability, public concerns and consumer demand, and legal and moral recognition across contexts, situating fish welfare within the ‘One Health’ and ‘One Welfare’ frameworks that link animal welfare, environmental stewardship and human well‐being. Ongoing challenges include climate change, cultural factors and the interpretation of fish sentience and cognition among others.

A SAFER Model for Accurately Estimating Actual Evapotranspiration in Sugarcane Using Sentinel-2 - Alberto Mario Arroyo Avilez; Julian David Ome Narváez; Julian Fernando Mateus-Rodriguez (Sugar Tech, 2026)

Comparative genome-wide association study shows single-nucleotide polymorphic loci associated with resistance to Meloidogyne incognita, Fusarium oxysporum f. sp. phaseoli, and their co-infection in common bean - Maria Laura Urbano Nascimento; César Júnior Bueno; Carlos Eduardo Rossi; Antônio Augusto Franco Garcia; Maria Lúcia Carneiro Vieira; Luís Eduardo Aranha Camargo; Alisson Fernando Chiorato; Sérgio Augusto Morais Carbonell; Monica Rodriguez; Luciana Lasry Benchimol-Reis (Planta, 2026)
Main conclusion The genetic architecture underlying co-infection with Meloidogyne incognita and Fusarium oxysporum f. sp. phaseoli differs from that observed when these pathogens are evaluated individually. Abstract Common bean ( Phaseolus vulgaris L.) yield is threatened by simultaneous infection with the root-knot nematode Meloidogyne incognita (Mi) and Fusarium oxysporum f. sp. phaseoli (Fop). Root-knot nematodes are believed to intensify the severity of Fusarium wilt in common bean, and specific genomic regions are understood to be associated with the host response, whether conferring susceptibility or resistance. To elucidate the genetic mechanisms of this interaction, phenotypic traits were evaluated in greenhouse trials, followed by associative mapping using a genome-wide association study (GWAS) approach. The plant material consisted of a core collection of 180 common bean genotypes from the Agronomic Institute (IAC, Campinas, Brazil) diversity panel. The effects of Fop and Mi were evaluated individually and in co-infection. Associative mapping was performed using the Bayesian information and linkage disequilibrium iteratively nested keyway (BLINK) model. When plants were infected with Mi, significant SNPs were detected on chromosomes Pv07, Pv08, and Pv10 based on gall counts. SNPs were detected on Pv05, Pv06, P10, and Pv11 in association with co-infection. Regions associated with egg mass count were detected on Pv02, Pv04, and Pv05. However, co-infection revealed SNPs on chromosomes P10 and Pv11. Three SNPs were associated with Fusarium wilt–two on Pv07 and one on Pv08. The genomic regions and markers associated with resistance to Mi and Fop provide new resources for advancing understanding of host–pathogen relationships in these important pathosystems.

Variation in Environmental Conditions and Biodiversity Between Contrasting Intertidal Habitats Across Multiple Spatial Scales on European Rocky Shores - Luca Rindi; Ludovica Pedicini; Iacopo Bertocci; Lisandro Benedetti‐Cecchi; Dan Smale; Fernando Tuya; Adriana Rodriguez; Mariachiara Chiantore; Valentina Asnaghi; Paolo Albicini; Rolf Karez; Dominique Davoult; et al. (Global Ecology and Biogeography, 2026)
Aim Foundation species sustain biodiversity by providing habitat, resources, and protection from environmental stress. However, their influence on environmental severity and variability and their role in shaping diversity across spatial scales remain poorly understood. We conducted a large‐scale study to assess how environmental conditions and community diversity vary between areas with and without canopy‐forming macroalgae across local to regional spatial scales. Location Latitudinal range from 28°34′N to 54°11′N, encompassing both the Northeast Atlantic and Western Mediterranean regions. Time Period 2019–2020. Major Taxa Studied Marine macroalgae and benthic invertebrates. Methods Using a standardised nested sampling design across 13 sites in two marine regions (the Northeast Atlantic and Western Mediterranean) we compared the intensity and variability of temperature and light intensity, as well as community α‐ and β‐diversity, between intertidal rocky areas with and without canopy‐forming macroalgae. Data were analysed by means of linear mixed‐effects models. Results There were regional differences in variations of environmental conditions between habitats: NE Atlantic macroalgal canopies were characterised by lower environmental extremes and variability—especially in summer—than open rock areas, whereas differences between habitats were small in the W Mediterranean. Likewise, differences in α‐ and β‐diversity between habitats were region‐specific and scale‐dependent: in the NE Atlantic, α‐diversity was higher in the presence of canopies than in open rock areas from local to regional scales, while β‐diversity decreased in canopy stands with increasing spatial scale. In the W Mediterranean, α‐diversity was higher under canopies than on open rock at the regional scale, whereas β‐diversity was higher under canopies at small to intermediate scales. Main Conclusions Our results support the view that key environmental conditions and biodiversity on intertidal rocky shores differ between areas characterised by the presence or absence of canopy‐forming macroalgae acting as foundation species, across a hierarchy of spatial scales.

Suboptimal responses to E2/P4-based timed AI protocols compromise pregnancy outcomes in fertile beef cattle: Roles of ovulation timing and semen viability - César Augusto Pinzón-Osorio; Thomaz Kranen Cunha; German Holguin-Sanabria; Marco Alves Machado; Favorino José de Freitas Collares; Luís Henrique de Aguiar; Paula Rodriguez-Villamil; Felipe Ledur Ongaratto; Eduardo Pradebom da Silva; Eduardo de Oliveira Sanguinet; Carolina Silveira da Silva; Daiane Mentz; et al. (Animal Reproduction Science, 2026)

Optical and random laser properties of the novel multifunctional endoxifen derivative (FLTX3) and its potential for the diagnosis of breast cancer resistance - Mario Diaz; Sergio de Armas-Rillo; Fernando Lobo; Daniel Pereda de Pablo; Kevin Soler-Carracedo; Pablo Delgado; Mitzi Rodriguez; Ana Canerina-Amaro; Catalina Valdes-Baizabal; Raquel Marín; Dácil Hernández; Alicia Boto; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Use of shotgun immunoproteomics for the development of protein vaccines against Edwardsiella piscicida - Kim L. Jacobsen; Matt J. Griffin; Brett S. Phinney; Michelle Salemi; Zeinab Yazdi; Sujita Balami; Caitlin E. Older; Cynthia C. Ware; Fernando Y. Yamamoto; Noor-ul Huda; Tania Rodriguez-Ramos; Brian Dixon; et al. (Fish & Shellfish Immunology, 2026)

Linking genomic and proteomic signatures to brain amyloid burden: insights from GR@ACE/DEGESCO - Raquel Puerta; Itziar de Rojas; Pablo García-González; Clàudia Olivé; Oscar Sotolongo-Grau; Ainhoa García-Sánchez; Fernando García-Gutiérrez; Laura Montrreal; Juan Pablo Tartari; Ángela Sanabria; Vanesa Pytel; Carmen Lage; et al. (Functional & Integrative Genomics, 2025)

Time to metastasis as a prognostic factor in metastatic urothelial carcinoma: results from the ARON-2 study - Renate Pichler; Gerald Klinglmair; Kirstin Binz; Enrique Grande; Alina Pirshtuk; Hideki Takeshita; Yüksel Ürün; Javier Molina-Cerrillo; Zin W. Myint; Alfonso Gómez de Liaño; Augusto Mota; Alessia Salfi; et al. (Clinical & Experimental Metastasis, 2025)

A Bayesian network and DEMATEL-ISM based approach for evaluating resilience: A case study in inland waterway port - Fernando Gonzalez-Solano; Gina Galindo; Daniel Romero-Rodriguez (Ocean & Coastal Management, 2025)

Evaluation of the efficacy of polymeric antigen BLSOmp31 formulated in a new cage-like particle adjuvant (ISPA YOLK) administered by parenteral or mucosal routes against Brucella ovis in rams - María Celeste Moran; Agostina Tammone Santos; Paula Dominguez; Lucila Moriones; María Victoria Nieto Farias; Laura Maté; Juan Agustín García; Tobias Kuhn; Fernando Alberto Paolicchi; María Andrea Fiorentino; Marcelo Gastón Rodriguez; Jorge Pablo García; et al. (Veterinary Immunology and Immunopathology, 2025)

Intact glycoconjugates from Taenia crassiceps excreted/secreted products ameliorate chemically induced colitis by modulating inflammation and strengthening adherens junctions - Yadira Ledesma-Soto; Ilse Chávez-Soto; Marissa Calderón-Torres; Andrea Monserrat Rodríguez-Lozoya; Jonadab E. Olguin; Luis B. Hernández-Portilla; César M. Flores-Ortíz; Fernando Candanedo; Miriam Rodriguez-Sosa; Sonia E. Hernández-Navia; Luis I. Terrazas (Inflammopharmacology, 2025)
Background Ulcerative colitis (UC) is a chronic inflammatory disease that is increasing in prevalence worldwide. Notably, helminth infections, known for their immunoregulatory properties, are inversely related to inflammatory conditions such as UC. Research has indicated that Taenia crassiceps infection can improve inflammatory-mediated diseases, including type 1 diabetes, experimental autoimmune encephalomyelitis, and colitis. Subsequent studies revealed that helminth-derived products can replicate the effects of complete infection in the context of inflammatory diseases; however, the mechanisms underlying these effects remain unclear. This study examined the impact of intact glycans from T. crassiceps excreted/secreted products (TcES) on host responses to dextran sodium sulfate (DSS)-induced colitis. Methods UC was induced by administering 4% DSS in the drinking water for 9 days. The mice were treated with intact TcES, glycan-depleted TcES, or protein-depleted TcES 2 days after colitis induction. Symptoms of the disease, along with immunologic and histopathological evaluations, were performed. Results Colitic mice that received intact TcES presented fewer disease symptoms and less histopathological damage. Intact TcES reduced the proinflammatory response while increasing the production of IL-4, IL-22, IL-31, and MCP-1 and promoting M2 macrophage polarization via PD-L2 expression. Furthermore, intact TcES diminished neutrophil infiltration, inhibited NF-κB and p38 phosphorylation in the colon, and suppressed reactive oxygen species and 3-nitrotyrosine levels, thus protecting the colon. These effects were accompanied by increased expression of E-cadherin and β-catenin, indicating improved epithelial barrier integrity. Conversely, mice treated with glycan-depleted or protein-depleted TcES exhibited exacerbated colitis characterized by disruption of colon tissue architecture, extensive inflammation, and epithelial damage, including loss of E-cadherin and β-catenin and a lack of M2 macrophage polarization. Conclusions Glycoconjugates on TcES play a significant role in mediating the immunomodulatory effects that alleviate DSS-induced colitis.

Constructed Wetlands and the role of the fungal community for wastewater treatment: A review - Letícia Mesacasa; Fernando Santos Cabral; Deison Antonio Taufer Fochi; Willian da Silva Oliveira; Fábio Oliveira; Mauricio Kersting; Gustavo Stolzenberg Colares; Adriane Lawisch Rodriguez; Carlos Alexandre Lutterbeck; Odorico Konrad; Ênio Leandro Machado (Ecohydrology & Hydrobiology, 2025)

Ecohydrological processes can predict biocrust cover at regional scale but not global scale - Ning Chen; Siqing Wang; Liping Yang; Defei Liang; Zhengwei Ren; Xudong Liu; Longwei Dong; Jingyao Sun; Emilio Rodriguez-Caballero; Bettina Weber; Caroline A. Havrilla; Emilio Guirado; et al. (Plant and Soil, 2025)

Association between PFAS exposure and metabolic-related biomarkers in Spanish adolescents - Andrea Rodriguez-Carrillo; Fernando Vela-Soria; Fatima Smagulova; Mariana F. Fernández; Carmen Freire (Environmental Research, 2025)

Zoonotic Parasites in Hoplosternum littorale Acquired in the Market of Santa Clara, in the City of Iquitos, Loreto-Peru - Germán Augusto Murrieta Morey; Stephanie Geovana Reyes Llanos; Luciano Alfredo Rodriguez Chu; Avita Celeste Taricuarima Dreyfus; Luis Armando García Solsol; Roger Fernando Chuquipiondo Sánchez; Ehrlich Yam Llasaca Calizaya (Acta Parasitologica, 2025)

Fosfomycin in bacteraemic urinary tract infection due to multidrug-resistant Escherichia coli : insights of post hoc DOOR analysis of the FOREST trial - Jesús Sojo-Dorado; Inmaculada López-Hernández; Belén Gutiérrez-Gutiérrez; Sandra De la Rosa-Riestra; Fernando Docobo-Pérez; Alicia Hernánez-Torres; Álvaro Pascual; Jesús Rodriguez-Baño; Esperanza Merino de Lucas; Laura Escolà-Vergé; Elena Bereciartua; Elisa García-Vázquez; et al. (Infectious Diseases, 2025)

A new opportunity for N-acetylcysteine. An outline of its classic antioxidant effects and its pharmacological potential as an epigenetic modulator in liver diseases treatment - Marina Galicia-Moreno; Hugo Christian Monroy-Ramirez; Fernando Caloca-Camarena; Scarlet Arceo-Orozco; Pablo Muriel; Ana Sandoval-Rodriguez; Jesús García-Bañuelos; Alejandro García-González; José Navarro-Partida; Juan Armendariz-Borunda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Exploring the potential of hydrolytic enzymes combined with antibacterial agents to disrupt pathogenic biofilms and disinfect released cells - Patricia Palafox-Rivera; Melvin R. Tapia-Rodriguez; Julio Cesar Lopez-Romero; Marco A. Lugo-Flores; Karen P. Quintero-Cabello; Brenda A. Silva-Espinoza; M. Reynaldo Cruz-Valenzuela; Filomena Nazzaro; J. Fernando Ayala-Zavala (Biofouling, 2025)

SAmMD: The South American mineral deposit database - Guilherme Ferreira da Silva; Martín Ricardo Gozalvez; Alonso Arturo Marchena; Anderson Dourado Rodrigues da Silva; Braulio Ignacio Aguila Aravena; Diego Jesús Rodriguez; Eduardo Linares; Edwin Fernando Gallardo Vargas; Franco Drausin Pinzon Rivas; Guillermo Lopez Aguilera; Jose Amado Rondon Muñoz; Juan Manuel Turra; et al. (Journal of South American Earth Sciences, 2025)

Improving generalization through self-supervised learning using generative pre-training transformer for natural gas segmentation - Luiz Fernando Trindade Santos; Marcelo Gattass; Carlos Rodriguez; Jan Hurtado; Frederico Miranda; Diogo Michelon; Roberto Ribeiro (Computers & Geosciences, 2025)

Molecular interplay of symbiotic and defensive responses in the non-model legume Arachis hypogaea - Johan Rodriguez; María Laura Tonelli; Adriana Fabra; Fernando Ibañez (Symbiosis, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Physicochemical changes in Amaranthus spp grains, flour, isolated starch, and nanocrystals during germination and malting - Elsa Gutiérrez-Cortez; Ezequiel Hernandez-Becerra; Luis Fernando Zubieta-Otero; Marcela Gaytán-Martínez; Oscar Yael Barrón-García; Mario Enrique Rodriguez-Garcia (Food Chemistry, 2024)

What's that smell? The putrid scent of Rafflesia consueloae, its origin and developmental regulation - Erika Marie A. Bascos; Edwino S. Fernando; Melizar V. Duya; Lillian Jennifer V. Rodriguez (Flora, 2024)

Influence of wildfires on the conflict (2006–2022) in eastern Ukraine using remote sensing techniques (MODIS and Sentinel-2 images) - Fernando Rodriguez-Jimenez; Ana Novo; Joanne V. Hall (Remote Sensing Applications: Society and Environment, 2024)

Glass fiber reinforced concrete: overview of mechanical and microstructural analysis - Sócrates Pedro Muñoz Pérez; Juan Fernando Santisteban Purizaca; Sandrita Maribel Castillo Matute; Juan Martín García Chumacero; Elver Sánchez Diaz; Edwin Adolfo Diaz Ortiz; Ernesto Dante Rodriguez Laffite; José Luis Quispe Osorio; Yander Mavila Briceño Mendoza (Innovative Infrastructure Solutions, 2024)

A Novel Digital Educational Strategy Improves Treatment Adherence and Quality of Life in Patients with Multiple Myeloma - Juan Guio; Andrés Melo; Mateo Mejía Saldarriaga; Cynthia Fuentes; Natalia Tíjaro-Ovalle; Andrés Borda; Yuli Guzmán; Elías Bolaños; Guillermo Quintero; Mónica Duarte; Claudia Agudelo; Soraya Aparicio; et al. (Journal of Cancer Education, 2024)

Effect of crumb rubber and steel slag on asphalt mixtures for a micropavement - Sócrates Pedro Muñoz Pérez; Jean Pierre Fernández Viera; Jeiner Fernando Gonzales Carranza; Luigi Italo Villena Zapata; Juan Martin Garcia Chumacero; Carlos Eduardo Ramos Brast; Edwin Adolfo Diaz Ortiz; Ernesto Dante Rodriguez Laffite (Innovative Infrastructure Solutions, 2024)

Plasma-grafting surface modifications to enhance membrane hydrophobicity for brine membrane distillation - Hugo Giraldo-Mejía; Yurieth M. Quintero; Francisca Mery; Fernando Rodriguez; Efrem Curcio; Humberto Estay; Andreina Garcia (Desalination, 2023)

Modelling of live fuel moisture content in different vegetation scenarios during dry periods using meteorological data and spectral indices - Fernando Rodriguez-Jimenez; Henrique Lorenzo; Ana Novo; Carolina Acuña-Alonso; Xana Alvarez (Forest Ecology and Management, 2023)

Impressions of the scientific training in fishery and aquaculture biotechnology in Mar del Plata, Argentina: Communication, networking, and multidisciplinary research - Ângelo Paggi Matos; Andressa Coimbra Pereira; Alejandro Perretta; Patricia Romero-Murillo; Luciana Melisa Del Gobbo; Emily Sol Garcia Martinez; Samuel Hilevski; Lucas Roberto Sepúlveda; Agustín Fernando Boan; Daniela Sartoni; Daiana Yanel Pereyra; Lucia García Martínez; et al. (Aquaculture, 2023)

Biochemical conditions for anaerobic digestion of agricultural feedstocks: A full-scale study linking elements concentration and residual methane potential - Mirco Garuti; Erika Sinisgalli; Mariangela Soldano; Antonia Jimenez Rodriguez; Fernando G. Fermoso (Biomass and Bioenergy, 2023)

Coastal raptors and raiders: New bird tracks in the Pleistocene of SW iberian Peninsula - Carlos Neto de Carvalho; João Belo; Silvério Figueiredo; Pedro P. Cunha; Fernando Muñiz; Zain Belaústegui; Mário Cachão; Joaquín Rodriguez-Vidal; Luis M. Cáceres; Andrea Baucon; Andrew S. Murray; Jan-Pieter Buylaert; et al. (Quaternary Science Reviews, 2023)

Contribution of TGFß and of a cocktail of TGFß and the pro-inflammatory cytokines IL-1, IL- 6 and TNFα to the establishment of a fibrotic phenotype in endometrial fibroblasts of mares - Yat S. Wong; Pamela Poblete; Lidice Mendez; Ana C. Mancanares; Lleretny Rodriguez-Alvarez; Fernando E. Saravia; Fidel O. Castro (Journal of Equine Veterinary Science, 2023)

Embryo biopsy and vitrification applied to a commercial embryo transfer program in Argentina - Fernando L Riera; Jaime E Roldán; Maria B Rodriguez; Fernando A Jastrzebski; Monique Lopez Echeverria; Katrin Hinrichs (Journal of Equine Veterinary Science, 2023)

Biological control of pathogens in artisanal cheeses - Sarahi del Carmen Rangel-Ortega; Lizeth Guadalupe Campos-Múzquiz; Ana Verónica Charles-Rodriguez; Mónica Lizeth Chávez-Gonzaléz; Lissethe Palomo-Ligas; Juan Carlos Contreras-Esquivel; José Fernando Solanilla-Duque; Adriana Carolina Flores-Gallegos; Raúl Rodríguez-Herrera (International Dairy Journal, 2023)

Emerging themes and future directions in watershed resilience research - Fernando Miralles-Wilhelm; John H. Matthews; Nathan Karres; Robin Abell; James Dalton; Shi-Teng Kang; Junguo Liu; Romain Maendly; Nathanial Matthews; Robert McDonald; Raúl Muñoz-Castillo; Boris F. Ochoa-Tocachi; et al. (Water Security, 2023)

Kisspeptin as potential biomarker of environmental chemical mixture effect on reproductive hormone profile: A pilot study in adolescent males - Andrea Rodriguez-Carrillo; Sylvie Remy; Shereen Cynthia D'Cruz; Elena Salamanca-Fernandez; Fernando Gil; Pablo Olmedo; Vicente Mustieles; Fernando Vela-Soria; Kirsten Baken; Nicolás Olea; Fátima Smagulova; Mariana F. Fernandez; et al. (Science of The Total Environment, 2023)

Assessment of Health Risk and Presence of Metals in Water and Fish Samples from Doce River, Brazil, After Fundão Dam Collapse - Amanda Oliveira Mourão; Mayra Soares Santos; Alexandre Sylvio Vieira da Costa; Heberson Teixeira da Silva; Luiz Fernando Oliveira Maia; Márcia Cristina da Silva Faria; Mariandry del Vale Rodriguez Rodriguez; Jairo Lisboa Rodrigues (Archives of Environmental Contamination and Toxicology, 2023)

Plant-based diets and risk of frailty in community-dwelling older adults: the Seniors-ENRICA-1 cohort - Javier Maroto-Rodriguez; Mario Delgado-Velandia; Rosario Ortolá; Adrián Carballo-Casla; Esther García-Esquinas; Fernando Rodríguez-Artalejo; Mercedes Sotos-Prieto (GeroScience, 2023)
Frailty is a geriatric syndrome that leads to increased risk of hospitalization, disability, and death. The effect of plant-based diets defined by the quality of their plant foods is unclear. Our objective is to study the association between two plant-based diet indices and the occurrence of frailty among community-dwelling older adults in Spain. We analyzed data from 1880 individuals aged ≥ 60 years from the Spanish Seniors ENRICA-1 cohort. We used a validated diet history to build two indices: (a) the healthful Plant-based Diet Index (hPDI) where healthy plant foods received positive scores, whereas less-healthy plant foods and animal foods received reverse scores; and (b) the unhealthful Plant-based Diet Index (uPDI), with positive scores to less-healthy plant foods and reverse scores to animal and healthy plant foods. Incident frailty was defined with the Fried phenotype. Study associations were summarized with odds ratios (OR) and 95% confidence intervals (CI) obtained from multivariable logistic models. After 3.3 years of follow-up, 136 incident frailty cases were ascertained. Comparing the highest vs. the lowest tertile of adherence, the OR [95% CI] for frailty was 0.43 (0.25–0.74; p- trend = .003) for the hPDI, and 2.89 (1.73–4.84; p- trend < .001) for the uPDI. Higher consumption of healthy plant foods was inversely associated with frailty (0.39 [0.23–0.66; p -trend < 0.001]); higher consumption of unhealthy plant foods was associated with higher frailty risk (2.40 [1.23–4.71; p -trend = .01]). In older adults, the hPDI was associated with lower risk of frailty, while the opposite was found for the uPDI.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

A novel equation that incorporates the linear and hyperbolic nature of the force–velocity relationship in lower and upper limb exercises - Julian Alcazar; Fernando Pareja-Blanco; Carlos Rodriguez-Lopez; Hector Gutierrez-Reguero; Juan Sanchez-Valdepeñas; Pedro J. Cornejo-Daza; Ignacio Ara; Luis M. Alegre (European Journal of Applied Physiology, 2022)

Regulatory mechanisms behind the phenotypic plasticity associated with Setaria italica water deficit tolerance - Vanessa Fuentes Suguiyama; Jae Diana Paredes Rodriguez; Tatiane Cristina Nicomedio dos Santos; Bruno Silvestre Lira; Luis Alejandro de Haro; João Paulo Naldi Silva; Eduardo Leite Borba; Eduardo Purgatto; Emerson Alves da Silva; Nicolas Bellora; Fernando Carrari; Danilo da Cruz Centeno; et al. (Plant Molecular Biology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Prediction ability for growth and maternal traits using SNP arrays based on different marker densities in Nellore cattle using the ssGBLUP - Juan Diego Rodriguez Neira; Elisa Peripolli; Maria Paula Marinho de Negreiros; Rafael Espigolan; Rodrigo López-Correa; Ignacio Aguilar; Raysildo B. Lobo; Fernando Baldi (Journal of Applied Genetics, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Use of pooled serum samples to assess herd disease status using commercially available ELISAs - Juan Heberth Hernandez-Medrano; Luis Fernando Espinosa-Castillo; Ana D. Rodriguez; Carlos G. Gutierrez; Wendela Wapenaar (Tropical Animal Health and Production, 2021)
Pooled samples are used in veterinary and human medicine as a cost-effective approach to monitor disease prevalence. Nonetheless, there is limited information on the effect of pooling on test performance, and research is required to determine the appropriate number of samples which can be pooled. Therefore, this study aimed to evaluate the use of pooled serum samples as a herd-level surveillance tool for infectious production-limiting diseases: bovine viral diarrhoea (BVD), infectious bovine rhinotracheitis (IBR), enzootic bovine leukosis (EBL) and Neospora caninum (NC), by investigating the maximum number of samples one can pool to identify one positive animal, using commercial antibody-detection ELISAs. Four positive field standards (PFS), one for each disease, were prepared by pooling highly positive herd-level samples diagnosed using commercially available ELISA tests. These PFS were used to simulate 18 pooled samples ranging from undiluted PFS to a dilution representing 1 positive in 1,000 animals using phosphate-buffered saline as diluent. A 1:10 dilution of the PFS resulted in positive results for IBR, BVD and EBL. Moreover, for IBR and BVD, results were still positive at 1:100 and 1:30 dilutions, respectively. However, for NC, a lower dilution (8:10) was required for a seropositive result. This study indicates that, at herd-level, the use of pooled serum is a useful strategy for monitoring infectious diseases (BVD, IBR and EBL) but not NC, using readily available diagnostic assays.

Molecular Correlates of Hemorrhage and Edema Volumes Following Human Intracerebral Hemorrhage Implicate Inflammation, Autophagy, mRNA Splicing, and T Cell Receptor Signaling - Marc Durocher; Bodie Knepp; Alan Yee; Glen Jickling; Fernando Rodriguez; Kwan Ng; Xinhua Zhan; Farah Hamade; Eva Ferino; Hajar Amini; Paulina Carmona-Mora; Heather Hull; et al. (Translational Stroke Research, 2021)
Intracerebral hemorrhage (ICH) and perihematomal edema (PHE) volumes are major determinants of ICH outcomes as is the immune system which plays a significant role in damage and repair. Thus, we performed whole-transcriptome analyses of 18 ICH patients to delineate peripheral blood genes and networks associated with ICH volume, absolute perihematomal edema (aPHE) volume, and relative PHE (aPHE/ICH; rPHE). We found 440, 266, and 391 genes correlated with ICH and aPHE volumes and rPHE, respectively ( p < 0.005, partial-correlation > |0.6|). These mainly represented inflammatory pathways including NF-κB, TREM1, and Neuroinflammation Signaling—most activated with larger volumes. Weighted Gene Co-Expression Network Analysis identified seven modules significantly correlated with these measures ( p < 0.05). Most modules were enriched in neutrophil, monocyte, erythroblast, and/or T cell-specific genes. Autophagy, apoptosis, HIF-1α, inflammatory and neuroinflammatory response (including Toll-like receptors), cell adhesion (including MMP9), platelet activation, T cell receptor signaling, and mRNA splicing were represented in these modules (FDR p < 0.05). Module hub genes, potential master regulators, were enriched in neutrophil-specific genes in three modules. Hub genes included NCF2, NCF4, STX3, and CSF3R, and involved immune response, autophagy, and neutrophil chemotaxis. One module that correlated negatively with ICH volume correlated positively with rPHE. Its genes and hubs were enriched in T cell-specific genes including hubs LCK and ITK, Src family tyrosine kinases whose modulation improved outcomes and reduced BBB dysfunction following experimental ICH. This study uncovers molecular underpinnings associated with ICH and PHE volumes and pathophysiology in human ICH, where knowledge is scarce. The identified pathways and hub genes may represent novel therapeutic targets.

Beginnings of a plant parasite: early development of Rafflesia consueloae inside its Tetrastigma host - Erika Marie A. Bascos; Edwino S. Fernando; Melizar V. Duya; Lillian Jennifer V. Rodriguez (Planta, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Adaptive mitochondrial response of the whiteleg shrimp Litopenaeus vannamei to environmental challenges and pathogens - Chrystian Rodriguez-Armenta; Orlando Reyes-Zamora; Enrique De la Re-Vega; Arturo Sanchez-Paz; Fernando Mendoza-Cano; Ofelia Mendez-Romero; Humberto Gonzalez-Rios; Adriana Muhlia-Almazan (Journal of Comparative Physiology B, 2021)

Analysis of urinary metabolites of polycyclic aromatic hydrocarbons in precarious workers of highly exposed occupational scenarios in Mexico - Lorena Díaz de León-Martínez; Rogelio Flores-Ramírez; Maribel Rodriguez-Aguilar; Alejandra Berumen-Rodríguez; Francisco J. Pérez-Vázquez; Fernando Díaz-Barriga (Environmental Science and Pollution Research, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

The pervasive and multifaceted influence of biocrusts on water in the world's drylands - David J. Eldridge; Sasha Reed; Samantha K. Travers; Matthew A. Bowker; Fernando T. Maestre; Jingyi Ding; Caroline Havrilla; Emilio Rodriguez‐Caballero; Nichole Barger; Bettina Weber; Anita Antoninka; Jayne Belnap; et al. (Global Change Biology, 2020)
The capture and use of water are critically important in drylands, which collectively constitute Earth's largest biome. Drylands will likely experience lower and more unreliable rainfall as climatic conditions change over the next century. Dryland soils support a rich community of microphytic organisms (biocrusts), which are critically important because they regulate the delivery and retention of water. Yet despite their hydrological significance, a global synthesis of their effects on hydrology is lacking. We synthesized 2,997 observations from 109 publications to explore how biocrusts affected five hydrological processes (times to ponding and runoff, early [sorptivity] and final [infiltration] stages of water flow into soil, and the rate or volume of runoff) and two hydrological outcomes (moisture storage, sediment production). We found that increasing biocrust cover reduced the time for water to pond on the surface (−40%) and commence runoff (−33%), and reduced infiltration (−34%) and sediment production (−68%). Greater biocrust cover had no significant effect on sorptivity or runoff rate/amount, but increased moisture storage (+14%). Infiltration declined most (−56%) at fine scales, and moisture storage was greatest (+36%) at large scales. Effects of biocrust type (cyanobacteria, lichen, moss, mixed), soil texture (sand, loam, clay), and climatic zone (arid, semiarid, dry subhumid) were nuanced. Our synthesis provides novel insights into the magnitude, processes, and contexts of biocrust effects in drylands. This information is critical to improve our capacity to manage dwindling dryland water supplies as Earth becomes hotter and drier.

Mislocalization of SMN from the I-band and M-band in human skeletal myofibers in spinal muscular atrophy associates with primary structural alterations of the sarcomere - María T. Berciano; María S. Castillo-Iglesias; J. Fernando Val-Bernal; Vanesa Lafarga; José C. Rodriguez-Rey; Miguel Lafarga; Olga Tapia (Cell and Tissue Research, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Intake, digestibility, and nitrogen balance in hair sheep fed Pennisetum purpureum supplemented with tropical tree foliage - Hassem Rodriguez-Villanueva; José Puch-Rodríguez; Juan Muñoz-González; José Sanginés-García; Edgar Aguilar-Urquizo; Alfonso Chay-Canul; Fernando Casanova-Lugo; Guillermo Jiménez-Ferrer; José Alayon-Gamboa; Angel Piñeiro-Vázquez (Agroforestry Systems, 2020)

Environmental factors driving the distribution of the tropical coral Pavona varians : Predictions under a climate change scenario - Laura Rodriguez; Juan José García; Fernando Tuya; Brezo Martínez (Marine Ecology, 2020)
Climate change causes shifts in the geographical distribution boundaries of many organisms. Modelling techniques predict the distribution of species by relating climatic and physical factors with species' presence records, including potential extinction areas and new potential areas of colonization, under predicted climatic scenarios. In this study, we initially explored which environmental variables most influenced the distribution of Pavona varians , a hermatypic coral from the equatorial Indian and the Pacific Ocean, which is categorized as ‘Least Concern’ by the UICN. The most influential variables were the minimum and maximum sea surface temperature, the diffuse water attenuation and the cloud cover. These variables were used to predict habitat suitability of P. varians under a current and a future (A1B IPPC) scenario using MaxEnt. Despite P. varians is an opportunistic species, with a well‐known resistance to environmental stress, the model predicted a massive decline in the suitability of its habitat in all areas by the year 2100. The information obtained by this study can be used to support the conservation decision making process to improve the preservation of the species.

Antifungal activity of Copaíba resin oil in solution and nanoemulsion against Paracoccidioides spp. - Lívia do Carmo Silva; Meire Ane Costa Miguel Miranda; Julianna Veiga de Freitas; Sarah Fernanda Araújo Ferreira; Emília Celma de Oliveira Lima; Cecilia Maria Alves de Oliveira; Lucilia Kato; Ana Paula Terezan; Anselmo Fortunato Ruiz Rodriguez; Fernando Sergio Escócio Drumond Via Faria; Célia Maria de Almeida Soares; Maristela Pereira (Brazilian Journal of Microbiology, 2020)

Atlantic corals under climate change: modelling distribution shifts to predict richness, phylogenetic structure and trait-diversity changes - Laura Rodriguez; Brezo Martínez; Fernando Tuya (Biodiversity and Conservation, 2019)

Reorganization of the nuclear compartments involved in transcription and RNA processing in myonuclei of type I spinal muscular atrophy - María S. Castillo-Iglesias; María T. Berciano; J. Oriol Narcis; J. Fernando Val-Bernal; José C. Rodriguez-Rey; Olga Tapia; Miguel Lafarga (Histochemistry and Cell Biology, 2019)

Degradation of haloacetic acids with the Fenton-like and analysis by GC-MS: use of bioassays for monitoring of genotoxic, mutagenic and cytotoxic effects - Amanda Oliveira Mourão; Diego Francis Silva; Mariandry Rodriguez; Thamyris Souza Torres; Elton Santos Franco; Valter Lúcio Pádua; Márcia Cristina da Silva Faria; Luiz Fernando Oliveira Maia; Jairo Lisboa Rodrigues (Environmental Monitoring and Assessment, 2019)

Phylogenomics of Enterococcus faecalis from wild birds: new insights into host‐associated differences in core and accessory genomes of the species - Ricardo León‐Sampedro; Rosa del Campo; Mercedes Rodriguez‐Baños; Val F. Lanza; María José Pozuelo; Carlos Francés‐Cuesta; Ana P. Tedim; Ana R. Freitas; Carla Novais; Luísa Peixe; Rob J. L. Willems; Jukka Corander; et al. (Environmental Microbiology, 2019)
Summary Wild birds have been suggested to be reservoirs of antimicrobial resistant and/or pathogenic Enterococcus faecalis ( Efs ) strains, but the scarcity of studies and available sequences limit our understanding of the population structure of the species in these hosts. Here, we analysed the clonal and plasmid diversity of 97 Efs isolates from wild migratory birds. We found a high diversity, with most sequence types (STs) being firstly described here, while others were found in other hosts including some predominant in poultry. We found that pheromone‐responsive plasmids predominate in wild bird Efs while 35% of the isolates entirely lack plasmids. Then, to better understand the ecology of the species, the whole genome of fivestrains with known STs (ST82, ST170, ST16 and ST55) were sequenced and compared with all the Efs genomes available in public databases. Using several methods to analyse core and accessory genomes (AccNET, PLACNET, hierBAPS and PANINI), we detected differences in the accessory genome of some lineages (e.g. ST82) demonstrating specific associations with birds. Conversely, the genomes of other Efs lineages exhibited divergence in core and accessory genomes, reflecting different adaptive trajectories in various hosts. This pangenome divergence, horizontal gene transfer events and occasional epidemic peaks could explain the population structure of the species.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Differential Susceptibility of Wild and Cultivated Blueberries to an Invasive Frugivorous Pest - Cesar Rodriguez-Saona; Kevin R. Cloonan; Fernando Sanchez-Pedraza; Yucheng Zhou; M. Monica Giusti; Betty Benrey (Journal of Chemical Ecology, 2019)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Antidiabetic Polypill Improves Central Pathology and Cognitive Impairment in a Mixed Model of Alzheimer’s Disease and Type 2 Diabetes - Carmen Infante-Garcia; Juan Jose Ramos-Rodriguez; Carmen Hierro-Bujalance; Esperanza Ortegon; Eleanor Pickett; Rosemary Jackson; Fernando Hernandez-Pacho; Tara Spires-Jones; Monica Garcia-Alloza (Molecular Neurobiology, 2018)

Seismotectonics of south-west Dominican Republic using recent data - Javier Rodriguez; Jens Havskov; Mathilde Bøttger Sørensen; Luis Fernando Santos (Journal of Seismology, 2018)

ATLANTIC AMPHIBIANS : a data set of amphibian communities from the Atlantic Forests of South America - Maurício Humberto Vancine; Kauã da Silva Duarte; Yuri Silva de Souza; João Gabriel Ribeiro Giovanelli; Paulo Mateus Martins‐Sobrinho; Ariel López; Rafael Parelli Bovo; Fábio Maffei; Marília Bruzzi Lion; José Wagner Ribeiro Júnior; Ricardo Brassaloti; Carolina Ortiz Rocha da Costa; et al. (Ecology, 2018)
Amphibians are among the most threatened vertebrates in the world and this is also true for those inhabiting the Atlantic Forest hotspot, living in ecosystems that are highly degraded and threatened by anthropogenic activities. We present a data set containing information about amphibian communities sampled throughout the Atlantic Forest Biome in South America. The data were extracted from 389 bibliographic references (articles, books, theses, and dissertations) representing inventories of amphibian communities from 1940 to 2017. The data set includes 17,619 records of 528 species with taxonomic certainty, from 1,163 study sites. Of all the records, 14,450 (82%) were classified using the criterion of endemism; of those, 7,787 (44%) were considered endemic and 6,663 (38%) were not. Historically, multiple sampling methods were used to survey amphibians, the most representative methods being active surveys (82.1%), surveys at breeding sites (20%), pitfall traps (15.3%), and occasional encounters (14.5%). Species richness averaged 15.2 ± 11.3 (mean ± SD) , ranging from 1 to 80 species per site. We found a low dominance in the communities, with 10 species occurring in about 26% of communities: Physalaemus cuvieri (4.1%), Dendropsophus minutus (3.8%), Boana faber (3.1%), Scinax fuscovarius (2.8%), Leptodactylus latrans (2.7%), Leptodactylus fuscus (2.6%), Boana albopunctata (2.3%), Dendropsophus nanus (1.6%), Rhinella ornata (1.6%), and Leptodactylus mystacinus (1.6%). This data set represents a major effort to compile inventories of amphibian communities for the Neotropical region, filling a large gap in the data on the Atlantic Forest hotspot. We hope this data set can be used as a credible tool in the proposal of new studies on amphibian sampling and even in the development of conservation planning for these taxa. This information also has great relevance for macroecological studies, being foundational for both conservation and restoration strategies in this biodiversity hotspot. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching events.

Total petroleum hydrocarbons and heavy metals in road-deposited sediments in Tijuana, Mexico - Analy Quiñonez-Plaza; Fernando Toyohiko Wakida; Juan Temores-Peña; Diana Dolores Rodriguez-Mendivil; Enrique Garcia-Flores; Miguel Angel Pastrana-Corral; Samuel Guillermo Melendez-Lopez (Journal of Soils and Sediments, 2017)

Erratum to: Economic risk assessment of Cotopaxi volcano, Ecuador, in case of a future lahar emplacement - Fabian Rodriguez; Theofilos Toulkeridis; Washington Sandoval; Oswaldo Padilla; Fernando Mato (Natural Hazards, 2017)

Economic risk assessment of Cotopaxi volcano, Ecuador, in case of a future lahar emplacement - Fabian Rodriguez; Theofilos Toulkeridis; Washington Sandoval; Oswaldo Padilla; Fernando Mato (Natural Hazards, 2017)

Using entropy theory to improve the definition of homogeneous regions in the semi-arid region of Brazil - Renata D.G. Rodriguez; Vijay P. Singh; Fernando F. Pruski; Arthur T. Calegario (Hydrological Sciences Journal, 2016)

Intervention trial with calcium montmorillonite clay in a south Texas population exposed to aflatoxin - Brad H. Pollock; Sarah Elmore; Amelia Romoser; Lili Tang; Min-su Kang; Kathy Xue; Marisa Rodriguez; Nicole A. Dierschke; Holly G. Hayes; H. Andrew Hansen; Fernando Guerra; Jia-Sheng Wang; et al. (Food Additives & Contaminants: Part A, 2016)

Ovarian activity and estrus behavior in early postpartum cows grazing Leucaena leucocephala in the tropics - Maria Bottini-Luzardo; Carlos Aguilar-Perez; Fernando Centurion-Castro; Francisco Solorio-Sanchez; Armin Ayala-Burgos; Ruben Montes-Perez; David Muñoz-Rodriguez; Juan Ku-Vera (Tropical Animal Health and Production, 2015)

Maintaining Antioxidant Potential of Fresh Fruits and Vegetables After Harvest - Jose A. Villa-Rodriguez; H. Palafox-Carlos; Elhadi M. Yahia; J. Fernando Ayala-Zavala; Gustavo A. Gonzalez-Aguilar (Critical Reviews in Food Science and Nutrition, 2015)

Discriminative stimulus and hypothermic effects of some derivatives of the nAChR agonist epibatidine in mice - Jesse S. Rodriguez; Colin S. Cunningham; Fernando B. Moura; Pauline Ondachi; F. Ivy Carroll; Lance R. McMahon (Psychopharmacology, 2014)

Quetiapine extended-release (Seroquel-XR) versus amitriptyline monotherapy for treating patients with fibromyalgia: a 16-week, randomized, flexible-dose, open-label trial - Elena P. Calandre; Fernando Rico-Villademoros; Jaime Galán; Rocio Molina-Barea; Juan S. Vilchez; Carmen M. Rodriguez-Lopez; Javier Hidalgo-Tallon; Piedad Morillas-Arques (Psychopharmacology, 2014)

Adenovirus and Norovirus Contaminants in Commercially Distributed Shellfish - Jesus Rodriguez-Manzano; Ayalkibet Hundesa; Byron Calgua; Anna Carratala; Carlos Maluquer de Motes; Marta Rusiñol; Vanessa Moresco; Ana Paula Ramos; Fernando Martínez-Marca; Miquel Calvo; Celia Regina Monte Barardi; Rosina Girones; et al. (Food and Environmental Virology, 2014)

Co-expression of the Bcl-xL antiapoptotic protein enhances the induction of Th1-like immune responses in mice immunized with DNA vaccines encoding FMDV B and T cell epitopes - Sultan Gülçe İz; Mert Döşkaya; Belen Borrego; Fernando Rodriguez; Yüksel Gürüz; İsmet Deliloğlu Gürhan (Veterinary Research Communications, 2013)

Peach palm (Bactris gasipaes) in tropical Latin America: implications for biodiversity conservation, natural resource management and human nutrition - Sophie Graefe; Dominique Dufour; Maarten van Zonneveld; Fernando Rodriguez; Alonso Gonzalez (Biodiversity and Conservation, 2013)

Effect of the Antimicrobial Peptide Tritrpticin on the In Vitro Viability and Growth of Trichomonas vaginalis - Veronica V. Infante; Alma D. Miranda-Olvera; Luis M. De Leon-Rodriguez; Fernando Anaya-Velazquez; Mayra C. Rodriguez; Eva E. Avila (Current Microbiology, 2011)

Role of cannabis and endocannabinoids in the genesis of schizophrenia - Emilio Fernandez-Espejo; Maria-Paz Viveros; Luis Núñez; Bart A. Ellenbroek; Fernando Rodriguez de Fonseca (Psychopharmacology, 2009)

Oriented Immobilization of Anti-Pneumolysin Tagged Recombinant Antibody Fragments - Maria del Mar Garcia-Suarez; Roberto Villaverde; Irene Gonzalez-Rodriguez; Fernando Vazquez; Francisco J. Mendez (Current Microbiology, 2009)

Short-Term Accumulation of Atrazine by Three Plants from a Wetland Model System - Eduardo Cejudo-Espinosa; Ana Carmela Ramos-Valdivia; Fernando Esparza-García; Patricia Moreno-Casasola; Refugio Rodriguez-Vazquez (Archives of Environmental Contamination and Toxicology, 2009)

Effect of growth temperature and pH on the aminopeptidase activity of Pseudomonas putida, P. fluorescens and Flavobacterium odoratum; the 4-nitroaniline test is reliable - L. A. Lopez-Tomas; J. A. Ordoñez; C. Mediavilla; J. L. Rodriguez-Marin; P. Sarmiento; A. Zamora; G. Garcia de Fernando (Folia Microbiologica, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Raptors as Indicators of Environmental Change in the Scrub Habitat of Baja California Sur, Mexico - Ricardo Rodriguez-Estrella; Jose Antonio Donazar; Fernando Hiraldo (Conservation Biology, 1998)